Psychological distress and quality of life in breast cancer survivors with taxane-induced peripheral neuropathy: A scoping review - Lauren Schwab; Constance Visovsky (Frontiers in Oncology, 2023)
PurposeThis review provides an assessment of psychological distress (depressive symptoms and anxiety symptoms) and the impact on quality of life in breast cancer survivors with chemotherapy-induced peripheral neuropathy induced by taxane-based chemotherapy.MethodsThe databases PubMed, CINAHL, Embase, and PsychInfo were searched for publications about psychological distress symptoms in breast cancer survivors with chemotherapy-induced peripheral neuropathy from taxane chemotherapy and the impact on quality of life.ResultsOnly eight studies were identified that addressed psychological distress symptoms in BCS with CIPN treated with taxane chemotherapy and the impact of these symptoms on QOL. Of these studies, a majority reported increased symptoms of psychological distress (depressive symptoms and/or anxiety symptoms) in BCS with CIPN. Researchers found that the persistent nature of CIPN and severity of symptoms resulted in decreased QOL.ConclusionsThis review highlighted a notable lack of research on psychological distress (depressive symptoms and anxiety symptoms) in BCS with CIPN. Furthermore, there was a gap in knowledge in how this psychological distress impacts QOL in this population. Further research is needed to better understand the extent that BCS with CIPN experience symptoms of psychological distress and the impact on QOL. This research would enable researchers to develop interventions focused on decreasing and potentially preventing these symptoms in BCS with CIPN treated with taxane chemotherapy, thereby decreasing the impact on QOL.